The effects of formula milk on development, nutrient absorption, and immune characteristics of piglets - Chuang Tang; Zhengjiang Liu; Lu Lu; Bo Zeng; Zhi Li; Ruohan Yang; Duoduo Zhang; Xiaolan Fan; Jiaxue Cao; Haohuan Li; Jing Sun; Jinwei Zhang; et al. (BMC Genomics)
Abstract Background Breast milk is widely regarded as the optimal nourishment for infants. However, due to physiological or psychosocial factors, many infants do not receive adequate breastfeeding. So, the formula milk is proposed as a substitute of breast milk, and an increasing number of infants are being formula-fed. Numerous studies have highlighted the difference between breast and formula feeding, but the underlying mechanisms remain elusive. Given the ethical constraints in conducting experimental studies on human breastfeeding, we employed pig, which have similar physiological structure with humans, to examine the impacts of different feeding practices. Results In this study, we found that effects of feeding practices were primarily associated with absorption, immunity, and the intestinal barrier. Compared to breast-fed piglets, formula-fed piglets had higher body weight (P = 3.31 × 10−2), liver weight (P = 6.57 × 10−8) and kidney weight (P = 4.40 × 10−6), but no differences in intestinal villus length and crypt depth. Formula feeding also enhanced the expression of transport genes relate to carbohydrates, amino acids, fatty acids, bile salts, vitamins, water, and calcium. Meanwhile, piglets fed with breast milk and formula milk demonstrated distinct immune characteristics. Breast milk promoted the expression of genes associated with immunity and the intestinal barrier. Breast-fed piglets had higher levels of IgM (P = 1.59 × 10−2), IgG (P = 3.17 × 10−2) and white blood cells (P = 6.72 × 10−3) in serum, as well as higher content of B cells (P = 4.08 × 10−6) and mast cells (P = 2.04 × 10−6) in the intestine. In contrast, formula-fed piglets showed higher levels of CD8+ T cells in intestine (P = 1.49 × 10−4). Conclusions In summary, this study comprehensively investigated the effects of feeding practice on piglet at the molecular level and provided valuable data for the development and application of formula milk.